Co-pyrolysis of pre-treated biomass and wastes to produce added value liquid compounds - Pinto, Filomena (2018)
ABSTRACT: It is imperative to find novel environmental friendly liquid fuels to be used in the long distance transportation sector. Pyrolysis of wastes may have an important role in the near future to attain this goal. Biomass pyrolysis has also been widely studied by several researchers, but besides the potentialities of such technology, the bio-oil obtained still has to overcome some challenges related to its unsuitable properties to be used in conventional combustion devices. On the contrary, plastics pyrolysis produces oils, whose main compounds are hydrocarbons, thus they can be used in conventional engines without complex and high cost upgrading processes. Thus, co-pyrolysis of plastics blended with biomass may be a suitable option to produce alternative liquid fuels from wastes. The biomass selected for this study was Eucalyptus globulus wastes, because it has been mostly used in the pulp and paper industry in Iberian Peninsula, which has produced high amounts of wastes. On the other hand, PE (polyethylene) was the plastic chosen, because of the huge wastes amounts generated per year. With the aim of facilitating biomass pyrolysis and to increase the production of liquid compounds with suitable properties to be used as fuels, an alternative to the conventional biomass pyrolysis was studied. First eucalyptus wastes were pre-treated by diluted acid hydrolysis, which removed the hemicellulose fraction, produced added value sugar-based compounds and upgraded the remaining solids to better conditions for pyrolysis. Several pathways were studied, including untreated and pre-treated eucalyptus, blended with different contents of PE wastes. The best technical option is the co-pyrolysis of pre-treated eucalyptus mixed with PE, as the highest liquids yields were produced. However, this process needs to be further studied and the economic viability of the overall process still needs to be proven.